Incidence and Risk Factors of Acute Kidney Injury in Acute Stroke - in a Tertiary Care Hospital - Ray, Nitai Chandra; Chowdhury, Md Ayub Ali; Muqeet, Md Abdul; Hasan, Mahmud Javed; Roy, Ashutosh Saha; Sarkar, Santana Rani (Community Based Medical Journal, 2019)
Acute kidney injury (AKI) is a common complication after acute stroke. Multiple additional risk factors are also responsible for development of AKI during acute stroke. This cross sectional observational study was conducted with a total of 240 newly detected computed tomography (CT) confirmed acute stroke patients in Mymensingh Medical College Hospital with an aim to find out the incidence and risk factors of AKI in acute stroke. In this study, AKI developed in 15.42% of all types of acute stroke and more commonly in haemorrhagic stroke than in ischaemic stroke (23.44% vs. 12.50%, P<0.05). AKI was found more frequently (54.05%) in old >60 years age group and in male patients(17.93% vs. 11.58% & P>0.05). Again, AKI developed most commonly in chronic kidney disease (CKD) (33.33%, P<0.05) and then in diabetes mellitus (DM) (31.03%, P<0.05), in ischaemic heart disease (IHD) (28.11%, P<0.05), in hypertension (21.14%, P<0.05), in previous stroke (15.22%, P>0.05), in dyslipidaemia (13.33%, P>0.05), and in smoker (9.89%, P>0.05). Family history of (H/O) DM was present in 30.00% (P>0.05) and that of hypertension and kidney disease was present in 24.44% (P>0.05) and 25.00% (P>0.05) of stroke patients, respectively. Among the AKI patients, majority (70.27%) had hypertension and 37.84% had CKD, 29.73% had IHD. DM and smoker were 24.32%of each. Family H/O of hypertension, DM and kidney disease was present in 29.73%, 16.22% & 13.51 % of AKI patients, respectively. So, this study had identified several important risk factors of AKI, in particular age, sex, smoking, hypertension, DM, IHD, CKD and types of stroke. So, the risk score could be easily calculated to predict the risk of AKI in stroke patients. And thus to prevent the development of AKI is of utmost importance to reduce the related morbidity and mortality of acute stroke patients. A multicenter nationwide intensive research is needed to identify the precise mechanism, risk factors, their relation and actual outcome of AKI that develop in patients with acute stroke. CBMJ 2019 January: vol. 08 no. 01 P: 12-18